The effectiveness of gamification in the online and offline qualitative marketing research - Michał Ścibor-Rylski (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2021)
Gamified market research tools help to increase respondents' engagement and obtain more in- depth results. Up till now the effects of gamification have been tested in the offline environment. The COVID-19 pandemic changed the world of the qualitative research and also triggered a need to replicate some previously presented effects. The article shows the results of two experiments proving the effectiveness of gamified approach to the qualitative advertisement and product concept testing in an online environment. The experimental groups with a narrative context added to a question regarding the first impression after viewing an advertisement or reading a product concept provided more elaborated answers to the open-ended questions than the control groups with a standard task. What's important, for the advertisement test the effect was significant for both online and offline conditions, whereas in the case of the product concept test only the online variant proved the superiority of the gamified task.
Keywords: M31; M37; M30; 650; gamification; marketing research; online research